The Role of Laser Therapy in the Treatment of Diabetic Macular Edema (DME): A Review of Contemporary Methods and Clinical Outcomes - Wijata, Anna; Dutkiewicz, Justyna; Przybyłek-Stępień, Zuzanna Adriana; Bartosiński, Ryszard; Szustak, Jan; Wijata, Michał; Mączyńska, Wiktoria; Kąpa, Maria; Szepietowski, Bartosz; Kaźmierczak, Jakub; Rycerz, Ewelina (Journal of Education, Health and Sport, 2025)
Introduction: Diabetic macular edema (DME) is a leading cause of vision loss in patients with diabetic retinopathy. Laser therapy, used for many years in the treatment of DME, allows for the reduction of edema and protection of vision. Aim of the Study: The aim of this paper is to review the role of laser therapy in the treatment of DME, covering traditional methods such as panretinal and focal photocoagulation, as well as newer approaches like micropulse laser therapy. The paper also analyzes a comparison of laser therapy with other treatment methods, such as VEGF inhibitor injections and steroid therapies, highlighting the advantages and limitations of each. Challenges related to treatment precision and therapy resistance, as well as new technologies and future directions in the development of laser therapy for DME, will also be discussed. The goal is to provide a comprehensive overview of the role of laser therapy in DME treatment and its place in modern ophthalmologic practice. Materials and Methods: A literature review was conducted in databases such as PubMed, Scopus, Web of Science, and Google Scholar, using relevant keywords. The selection of studies was limited to those with full access to the content or available in open-access repositories. Conclusions: Diabetic macular edema (DME) remains a leading cause of vision loss in patients with diabetes, and effective treatment, including laser therapy and pharmacological therapies, is crucial for reducing edema and improving vision. The future of DME treatment lies in the integration of modern technologies, including artificial intelligence, VEGF therapy, and gene therapies, which could significantly improve treatment outcomes and reduce the number of required interventions.